Sentencing of Minor Offences in Indonesia: Policy, Practice and Reform - Susilowati, Christina Maya Indah (International Journal of Criminology and Sociology, 2021)
This paper seeks to evaluate minor offenses in the Criminal Code in Indonesia. So far, the value limit for determining minor offenses in Indonesia is increasingly irrelevant to the value of the currency due to inflation. It will cause a gap in criminal law in dealing with changes. As the result, police will do unfair and non-humanistic law implementation. The objective of this study is to identify the importance of revising the lower limit of minor offenses in the Criminal Code in Indonesia. The study used a socio-legal method on the contextualization of Indonesian Criminal Codes related to the categorization of minor offense regulation in Government Regulation No. 2 of 2012 and in Penal Code, by utilizing a humanitarian perspective in law enforcement, especially by police who still charge some minor offenses with 5 years imprisonment. The results confirmed that some changes have been made related to this matter as Indonesian Supreme Court has made some regulation, such as No. 2 of 2012 on adjustment in minor offense law. This means that all criminals doing minor offense cannot be hold as prisoners in the investigation or prosecution process. The main contribution of this study is to construct a perspective of legal and regulatory issues to emphasize a fair of justice in dealing with minor offenses with a model of humanistic law enforcement. The result is expected to practically contribute and recommend the importance of constructing fairness of justice principle in law enforcement in particular and of revising minor offence sentencing in general.